Management of Collective Duha Prayer Habits in Shaping Student Character: Insights from Indonesian High Schools - Atep Suryaman; Basnang Said (Jurnal Iman dan Spiritualitas, 2026)
This study aims to explore the management model applied in the habit of performing the Dhuha prayer as a means of developing religious character and discipline in students at the secondary school level, using a systemic approach based on POAC (Planning, Organizing, Actuating, Controlling). The approach used is descriptive qualitative with a multiple case study strategy, utilizing participatory observation techniques and document analysis to obtain valid and contextual data. The results of the study indicate that the habit of performing the Dhuha prayer significantly influences the development of discipline, the automatic cultivation of religiosity, and the stability of students' character, especially when this practice is managed systematically through careful planning, consistent implementation, and continuous evaluation. These findings have high relevance for the field of Islamic education management, the development of character-based curriculum, the formulation of school policies that emphasize religious culture, and the integration of ritual practices into the structure of formal education habitus. The strength of this study lies in presenting a management model for the habit of institutionalized sunnah worship, not just a ritual routine, while also introducing the concept of "automatic religiosity" that can strengthen religious practices internally within the school environment. This model is expected to be a reference for the development of students' religious character in a structured and sustainable manner.